Effects of High-Grain Diet With Buffering Agent on the Hepatic Metabolism in Lactating Goats - He, Meilin; Li, Lin; Wang, Huanhuan; Yan, Shuping; Zhang, Yuanshu (Frontiers in Physiology, 2019)
To gain insight on the effects of a high-grain diet with buffering agent on liver metabolism and the changes of plasma biochemical parameters and amino acids in hepatic vein and portal vein, commercial kit and high performance liquid chromatography (HPLC) were applied to determine the concentration of amino acids of hepatic vein and portal vein blood samples, quantitative real-time PCR and comparative proteomic approach was employed to investigate proteins differentially expressed in liver in lactating dairy goats fed high-grain diet with buffering agent or only high-grain diet. Results showed that feeding high-grain diet with buffering agent to lactating dairy goats could outstanding increase amino acid content of Gln (p<0.01), and the amino acid contents of Arg and Tyr in BG were significantly higher (p<0.05) than that in HG. After adding the buffering agent, the metabolism of amino acids in the liver was changed and most of the amino acids were increasingly synthesized and decreasingly consumed in the liver. In addition, 46 differentially expressed protein spots (≥1.5-fold changed) were detected in buffering group vs. control group using 2-DE technique and MALDI-TOF/TOF proteomics analyzer. Of these, 24 proteins showed increased expression and 22 proteins showed decreased expression in the buffer group vs. control group. Data on Gene Ontology (GO) analysis and KEGG pathway analysis reveals that the high-grain diet with buffering agent alter the expression of proteins related to amino acids metabolism and glycometabolism. In addition, the results conclude that feeding high-grain diet with buffering agent can strengthen anti-oxidant capacity, stress ability, slow down urea metabolism, and alter amino acid metabolism as well as glycometabolism in the liver through different detection methods including proteomic analysis, real-time PCR analysis and biochemical analysis.